Kinematic and dynamic analysis of the landing after a volleyball spike jump - van Husen, M.; Peikenkamp, K.; Nicol, K.
The landing process initiated at most subjects with a knee angle position between 160-170°. Extreme angle positions of 176° and 141° are rather the exception. The rate of the knee joint at this time depends on the subject and varies between 2,9-4,1 m/s. Subsequently, this rises still up to max. 5.7 m/s and is then completely braked. The knee angle normally becomes smaller thereby on values between 95-115°. However, it can be also under 80°. The values of the external load parameters vary clearly. Thus the passive maximum of the vertical ground reaction force varies between 2,9 and 8,8 bw. Just as differently the average and maximum loading rate are. Their values range between 29-702 bw/s and 140-1335 bw/s, respectively. A correlation between the load parameters and the kinematic values generally can not be proved. Only for individual subjects a few correlations are determined. The results show large differences between and within the subjects, which refer to a non-standard landing technique. Nevertheless it can be assumed due to these data that athlets are exposed to high loads during landings. In particular the analyzed parameters of the vertical ground reaction force can possibly lead to damages of the e.g. cartilage. For more accurate predications the determination of internal load parameters is necessary.